Rural Poverty in Developing Countries : Implications for Public Policy - Khan, Mahmood (Washington, D.C. : International Monetary Fund, 2003)
Reviews causes of poverty in rural areas and presents a policy framework for reducing rural poverty, including through land reform, public works programs, access to credit, physical and social infrastructure, subsidies, and transfer of technology. Identifies key elements for drafting a policy to reduce rural poverty.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet